Fact-finding and Upheaval in the field of Biometrics - Parashar, Abhishek; Ali, Arshad (International Journal of Psychosocial Rehabilitation, 2020)
There are many different types of techniques used for recording, saving and analyzing data for biometrics. Most of the techniques (Mobile Biometric Technology, Multimodal Biometric Authentication system, Cloud Based Biometric Solutions etc.) are used by the defense organizations such as police, army, banks etc. and as result the software’s and the techniques are not feasible for the private security organizations and local defense organizations. This paper deals with the innovation of a new and advanced software and hardware which can bring valuable changes in this field. The software will be basically for combination of data (fingerprint and eye retina) and will pick out the respective individual’s data who’s fingerprint or eye retina was given as input. and hardware will be for the advanced security of our system (PC, laptops, mobile phones etc.), high security rooms etc. by making the hardware compatible with the basic needs of today’s world’s concern regarding security which can be monitored and saved with fast functioning and more secure hardware. The hardware will be developed by keeping the security and privacy at highest level. The fingerprint sensor will be equipped with a mechanism to detect human heat and eye retina sensor will be compatible of capturing eye retina from a long distance and save the data as well on the same time.